Novel Cu(II), Ni(II), Zn(II), Cd(II), and Mg(II) complexes with a series of 2-arylhydrazono-1, 3-dicarbonyl compounds. Synthesis, structure and spectroscopic characteristics. (1st July 2020) - Kovalchukova, Olga V.; Anh, Vu Thi Ngoc; Utenyshev, Andrey N.; Stash, Adam I.; Ryabov, Mikhail A.; Abbas, Al Tahan Rana Abdulila; Voronkova, Violetta K.; Bazan, Leah V.
Graphical abstract: 12 novel complex compounds of Cu(II), Ni(II), Zn(II), Cd(II), and Mg(II) with four N -heterocyclic derivatives of 2-arylhydrazono-1, 3-dicarbonyl compounds as potential dyes and medical drugs are isolated and identified by FT IR, 1 H NMR, EPR, X-Ray structure analysis, and UV–Vis spectroscopy. The experimental data together with the DFT theoretic modeling allowed determine the type of coordination of the organic molecules and coordination polyhedra of the metal cations. Abstract: A series of novel metal complexes of Cu(II), Ni(II), Zn(II), Cd(II), and Mg(II) with four N -heterocyclic derivatives of 2-arylhydrazono-1, 3-dicarbonyl compounds were isolated and identified by FT IR, 1 H NMR, EPR, and UV–Vis spectroscopy. The crystallographic data for two organic ligands as well as Mg(II) and Ni(II) complexes were obtained. It was indicated that the organic species exist in the form of hydrazo-tautomers. The Ni complex is monomeric and is characterized by the tridentate coordination of the ligand through a deprotonated N -atom of the hydrazo-fragment and two neighboring O-atoms of the carbonyl and deprotonated hydroxy-groups. In the case of the Mg complex the polymeric structure is observed with the additional coordination through the sulfamide group of the organic specie. Formation constants of the complexes in ethanol aqueous solutions were calculated and correlated with some physical characteristics of the metal cations. Structures of yet unstudied metal complexes were proposed based on quantum-chemical modeling at the DFT/B3LYP level.